2004
DOI: 10.1007/s00248-003-2035-2
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Growth of a Natural Population of the Smallest Free-Living Eukaryote under Nitrogen Deficiency and Sufficiency

Abstract: The influence of dissolved inorganic nitrogen (DIN) enrichments on cell-normalized carbon uptake rate, chlorophyll a content, and apparent cell size of a picoeukaryote (<1 microm) ( Ostreococcus tauri, the smallest eukaryotic cell) from a natural summer phytoplanktonic assemblage (<200 microm) in a northern Mediterranean Lagoon (Thau Lagoon) was studied in 20-L enclosures in June 1995. The natural planktonic community was incubated in situ for 24 h with initial ammonium and nitrate enrichments and compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…7). Reports of growth rates for control and nutrient-amended field samples dominated by Ostreococcus range from 2 to 8 day Ϫ1 , with grazing losses in the range of 1.5 to 6.5 day Ϫ1 (27). High growth rates and grazing losses could explain the large month-to-month variability that we observed for Ostreococcus abundance.…”
Section: Discussionmentioning
confidence: 67%
“…7). Reports of growth rates for control and nutrient-amended field samples dominated by Ostreococcus range from 2 to 8 day Ϫ1 , with grazing losses in the range of 1.5 to 6.5 day Ϫ1 (27). High growth rates and grazing losses could explain the large month-to-month variability that we observed for Ostreococcus abundance.…”
Section: Discussionmentioning
confidence: 67%
“…Under appropriate conditions these green microalgae grow rapidly (18), but prasinoviruses are also present everywhere in marine waters, sometimes at high densities (3), and probably play a key role in the regulation of such populations by host cell lysis. However, despite their ecological importance, relatively little is known about these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the mutation rates per generation of dsDNA viruses are close to those estimated in multicellular species (11), and the first possibility seems unlikely although it has been shown that coevolution with viruses may speed up the mutation rate of the hosts in bacterial populations (32). Alternatively, in contrast to metazoans, prasinovirus hosts are fast-growing unicellular organisms that can divide more than once per day under favorable conditions (18), whereas the replication rate of viruses in the environment is unknown. Indeed, viral particles are stable in seawater in the laboratory over long periods (at least several months at 20°C and over 4 years at 4°C).…”
Section: Discussionmentioning
confidence: 99%
“…O. tauri was isolated from the shallow (4-m mean depth) and eutrophic Thau lagoon in the South of France, where this species has to cope with high irradiance and fluctuating light (Fouilland et al 2004;Lazure 1992). In contrast, O. sp.…”
Section: Discussionmentioning
confidence: 99%